NUA Activities at the Plant Nuclear Pore - Xu, Xianfeng Morgan (Landes Bioscience, 2007)
NUA (Nuclear Pore Anchor), the Arabidopsis homolog of Tpr (Translocated Promoter Region), is one of the few nuclear pore proteins conserved between animals, yeast and plants. In the May issue of Plant Cell, we report that null mutants of NUA show a pleiotropic, early flowering phenotype accompanied by changes in SUMo and RNA homeostasis. We have shown that the early flowering phenotype is caused by changed abundances of flowering time regulators involved in several pathways. Arabidopsis nua mutants phenocopy mutants lacking the ESD4 (EARlY IN ShoRT DAYS 4) SUMo protease, similar to mutants of their respective yeast homologs. however, in contrast to the comparable yeast mutants, ESD4 does not appear to be delocalized from the nuclear pore in nua mutants. Taken together, our experimental data suggests a role for NUA in controlling mRNA export from the nucleus as well as SUMo protease activity at the nuclear pore, comparable but not identical to its homologs in other eukaryotes. Furthermore, characterization of NUA illustrates a potential link at the nuclear pore between SUMo modification, RNA homeostasis and plant developmental control.